Use of oral creatine as an ergogenic aid for increased sports performance: perceptions of adolescent athletes - Ray, T. R.; Eck, J. C.; Covington, L. A.; Murphy, R. B.; Williams, R.; Knudtson, J. (Southern Medical Journal, 2001)
BACKGROUND: Competitive athletes, including adolescents, seek ways to gain advantage over competitors. One ergogenic aid is creatine, a naturally occurring nitrogen compound found primarily in skeletal muscle. Increasing creatine levels may prolong skeletal muscle activity, enhancing work output. METHODS: A questionnaire assessing awareness and use of creatine supplementation was completed by 674 athletes from 11 high schools. Data were statistically analyzed to determine variation among groups. RESULTS: Of those surveyed, 75% had knowledge of creatine supplements, and 16% used creatine to enhance athletic performance. Percentage of use increased with age and grade level. Awareness and use were greater among boys than girls. Adverse effects were reported by 26%. Most athletes consumed creatine using a method inconsistent with scientific recommendations. CONCLUSIONS: Use of creatine by adolescent athletes is significant and inconsistent with optimal dosing. Physicians, athletic trainers, and coaches should disseminate proper information and advise these adolescent athletes.